System of mustard intensificationPaving the way for India’s self-reliance in oilseed production - Kumar, Sandeep; Rathore, Sanjay Singh; Kumar, Avaneesh (Indian Farming, 2024)
The global vegetable oils sector, playing a crucial role in nutrition, energy, and economic stability, has witnessed a robust growth rate of 4.1% per annum over the last three decades. However, India faces a deficit of 14.1 million tonnes in edible oil, leading to increased import expenditures, reaching `150,800 crore in 2021–22. Escalating demand, driven by rising per capita income and consumption,necessitates innovative solutions to enhance productivity. System of Mustard Intensification (SMI) has recently caught attention of the cultivators in some not so traditional mustard growing areas of the country. Drawing inspiration from successful practices like the System of Rice Intensification, SMI optimizes mustard cultivation, emphasizing resource efficiency and minimal environmental impact. This technology has already been tested and performed well in the field experiments at the Indian Agricultural Research Institute, New Delhi, and in farmers' fields in Umariya, Madhya Pradesh. The system of mustard intensification stands as a promising agricultural innovation with the potential to address challenges in mustard cultivation, contribute to oilseeds production, and reduce import burdens. The positive outcomes observed in diverse regions underscore the importance of promoting and adopting SMI for sustainable and efficient mustard cultivation.